2015
DOI: 10.4149/neo_2015_050
|View full text |Cite
|
Sign up to set email alerts
|

Deltonin induced both apoptosis and autophagy in head and neck squamous carcinoma FaDu cell

Abstract: For decades, despite the advancement of medical science, the prognosis of head and neck squamous cell carcinoma (HNSCC), has not improved. Deltonin is one of the major active components of Dioscorea Zingiberensis Wright that has been used for anthrax, rheumatic heart disease, rheumatoid arthritis etc. By employing HNSCC FaDu cell and normal human epidermal keratinocyte, we investigate deltonin efficacy and associated mechanism in both cell culture and nude mice xenografts. Deltonin treatment selectively preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…These effects were concurrent with single gene up-regulation of the p21 gene CDKN1A, all of which are likely responsible for the observed cytostatic effects of WYE in a 6-day proliferation study. Our findings in this aspect support much of the existing literature for WYE and saponins from the Dioscorea species having the capacity to induce cell-cycle arrest (G 2 /M) across diverse cancer cell lines with observed downregulation of a similar list of cyclins and cell cycle regulatory transcripts (Cdc25C, Cdk1) (31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 87%
“…These effects were concurrent with single gene up-regulation of the p21 gene CDKN1A, all of which are likely responsible for the observed cytostatic effects of WYE in a 6-day proliferation study. Our findings in this aspect support much of the existing literature for WYE and saponins from the Dioscorea species having the capacity to induce cell-cycle arrest (G 2 /M) across diverse cancer cell lines with observed downregulation of a similar list of cyclins and cell cycle regulatory transcripts (Cdc25C, Cdk1) (31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 87%
“…Recently, drugtriggered Chk2 activation has been suggested to possess anticancer effects in HNSCC. Hu et al 53 described that the antitumor role of curcumin is related to ataxia telangiectasia muted protein (ATM)/CHK2 activation and nuclear factor-κB inhibition, whereas Xie et al 54 showed that deltonin treatment activated Chk1 and Chk2 and the caspase pathway, leading to cell cycle arrest and induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed compounds with the corresponding retention time and the measured accurate mass in negative or positive ion mode were listed in Additional file 1: Table S1. Among them, the compounds with a retention time of 7.862-8.017 min were identified as ellagitannin flavonoids, including TA, TB, PHG, PGHG, and other unidentified compounds, which are the main components in PCP [35,49,60]. In addition, the representative TIC in negative ion mode and UV chromatogram at 254 nm for PCP leaf and steam parts were displayed in Additional file 1: Fig.…”
Section: Characterization Of Pcpmentioning
confidence: 99%
“…It is commonly used as a kind of health tea in the local region [4,51]. Emerging modern pharmacological studies show that PCP extract and its derived components exert potent anti-oxidation, anti-tumor, liver protection, and other effects [3,4,20,22,60,65,66,70]. The chemical analysis of PCP demonstrated that the main components are polyphenols, including rutin, quercetin, and ellagitannin flavonoids [17,21,49].…”
Section: Introductionmentioning
confidence: 99%